Comparison of Male and Female Per Capita Expenditure in North Sumatra in 2025 Using the Maximum Likelihood Estimation Method - Eliza Margareth Pangaribuan; Santa Ceacilia Br Tarigan; Sintya Ester Z Berutu; Claudia Nainggolan (Penerbit Hellow Pustaka, 2026)
This study aims to analyze and compare per capita expenditure patterns between men and women in North Sumatra Province in 2025. Per capita expenditure is a crucial indicator reflecting the level of welfare, purchasing power, and economic capacity of the population in a region. Given that household consumption in North Sumatra continues to increase annually, identifying gender disparities in expenditure is essential for evaluating the equity of economic development. The method used in this study is Maximum Likelihood Estimation (MLE) to estimate the parameters of the expenditure distribution. MLE was chosen for its ability to provide consistent and efficient estimates, particularly with large sample sizes, under the assumption of specific data distributions such as the log-normal distribution commonly found in expenditure and income data. The research data is sourced from secondary data from the North Sumatra Provincial Central Statistics Agency for the year 2025. The results of the analysis are expected to map the extent of expenditure disparities between men and women across various regencies and cities in North Sumatra. These findings are expected to serve as a foundation for local governments in formulating more inclusive and gender-responsive policies to improve social welfare and reduce economic inequality in the region.